Environmental risk of mesothelioma in the United States: An emerging concern—epidemiological issues. (17th August 2016) - Baumann, Francine; Carbone, Michele
ABSTRACT: Despite predictions of decline in mesothelioma following the ban of asbestos in most industrial countries, the incidence is still increasing globally, particularly in women. Because occupational exposure to asbestos is the main cause of mesothelioma, it occurs four- to eightfold more frequently in men than women, at a median age of 74 years. When mesothelioma is due to an environmental exposure, the M:F sex ratio is 1:1 and the median age at diagnosis is 60 years. Studying environmental risk of mesothelioma is challenging because of the long latency period and small numbers, and because this type of exposure is involuntary and unknown. Individual-based methods cannot be used, and new approaches need to be found. To better understand the most recent trends of mesothelioma in the United States, all mesothelioma deaths reported to the Centers for Disease Control and Prevention (CDC) during 1999–2010 were analyzed. Among all mesothelioma deaths in the United States, the 1920s birth cohort significantly predominated, and the proportion of younger cohorts constantly decreased with time, suggesting a decline in occupational exposure in these cohorts. The M:F mesothelioma sex ratio fell with time, suggesting an increased proportion of environmental cases. Environmental exposures occur in specific geographic areas. At the large scale of a state, mesotheliomas related to environmental exposure are diluted among occupational cases. The spatial analysis at a smaller scale, such as county, enables detection of areas with higher proportions of female and young mesothelioma cases, thus indicating possible environmental exposure, where geological and environmental investigations need to be carried out.